Pelatihan Pemanfaatan Video Pembelajaran Interaktif Sebagai Salah Satu Sumber Belajar Peserta Didik Pada Guru-Guru SMP di Kecamatan Gunung Sugih Kabupaten Lampung Tengah - Yudisthira, Ardhi; Sinaga, Risma Margaretha; Perdana, Yusuf; Rachmedita, Valensy; Ewandari, Yustina Sri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The purpose of this community service activity is to provide teachers with knowledge and insight regarding interactive learning videos as a learning resource. Interactive learning videos are one of the tools that can be used in learning activities. Using videos in the learning process is an effective and dynamic alternative, especially in addressing low learning outcomes and a lack of conceptual understanding. The method used in this community service activity is direct training and mentoring for participating teachers, in this case junior high school teachers in Gunung Sugih District, Central Lampung Regency. The community service team hopes that this community service activity will achieve the goals planned by the community service team, namely the creation of interactive learning videos that can be used as a learning resource for students in the classroom. Furthermore, the community service team hopes to further disseminate information regarding the creation and use of interactive learning videos through the publication of scientific articles